Restoration of nephrosplenic colonic entrapment with conservative treatment in 4 horses - ZAMBOULI (Δ.Α. ΖΑΜΠΟΥΛΗ) D. A.; DIAKAKIS (Ν. ΔΙΑΚΑΚΗΣ) N.; PATSIKAS (Μ.Ν. ΠΑΤΣΙΚΑΣ) M. N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Nephrosplenic entrapment, or left dorsal displacement of the large colon, is a topographic abnormality of the left colon, which is displaced and entrapped over the nephrosplenic ligament. The purpose of this study was to present a conservative therapeutical scheme that led to the resolution of this rather common disease of the horse. Three geldings and one mare, with an age ranging from 9 to 14 years, were admitted with acute and severe colic associated with the absence of intestinal sounds on abdominal auscultation. The diagnosis of nephrosplenic entrapment in all these horses was based on rectal examination revealing bands of colon coming out of the nephrosplenic space and displacement of the pelvic flexure and spleen towards the midline and caudally. Abdominal ultrasonography, performed in two of the horses, confirmed the caudal displacement of the spleen and indirectly the tentative diagnosis. Resolution of nephrosplenic entrapment was achieved with repeated intravenous injections of a phenylephrine solution and institution of supportive treatment. Despite the guarded to poor prognosis, the nephrosplenic entrapment resolved by itself in a period lasting from 36 hours to 4 days after the initiation of the treatment. According to the results of this study, the repeated phenylephrine injections, along with close monitoring and supportive care, may lead to medical resolution of the colonic entrapment without surgical intervention.